The factors influencing on customer retention in tourism industry of Melaka / Izzatul Anis Zamri - Zamri, Izzatul Anis (Faculty of Business and Management, 2019)
Customer retention or customer revisit has been highlighted as an important research topic in competitive market of tourism destinations. Despite the considerable number of research on customer retention, it remains clear why people undertake repeat visits and what is the factor influence the respondents to be a repeat visitor. This research aims to identify factors influencing on customer retention in tourism industry of Melaka. The results of this study indicated that “cost” was the most factor influenced on customer retention in Melaka. Concerning their perception on customer retention, the study revealed that respondents were intent to revisit and recommended Melaka as a holiday destination to others.